PENGGUNAAN MEDIA SOSIAL TWITTER @TXTDARI PEMERINTAH SEBAGAI SALURAN PENYEBARAN BERITA DALAM MEMBENTUK OPINI PUBLIK - Shinta Hartini Putri; Leoni Oktavia Maharani (Universitas Informatika dan Bisnis Indonesia, 2021)
Nowadays, the use of social media is increasing along with the development of information and communication technology. Social media as a form of new media presence brings many changes and impacts on people's social life, and even affects the effectiveness of the dissemination of news from the mass media. When viewed further, social media is now not only a means of socializing and seeking entertainment, but more than that social media is a public space that allows the public to know, give opinions, correct and criticize all forms of information or issues that occur around them so that they can be created. a public opinion. In this study, one of the Twitter social media accounts, @txtdarigovernment, will be analyzed which is considered to have an influence on the effectiveness in the dissemination of political news and the formation of public opinion. To sharpen the research, this research will refer to the factors that trigger public opinion according to Hennesy. This study uses descriptive qualitative research methods, with primary data collection techniques through observation through the Twitter account @txtdaripemerintah, while secondary data uses library research, journals, and internet sources. The output of this research will be published in the Artcomm Online Journal of the UNIBI Faculty of Communication and Design. The target of research results is expected to be able to complete and analyze data in the research environment or equivalent to level 5.